Correlation of Linear Body Size With Body Condition Score and Body Weight of Participated Cow Used in the Progeny Test in East Java - Larasati, Rizka; Susilorini, Tri Eko; Surjowardojo, Puguh; Wahyuni, Rini Dwi (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2024)
This study aims to analyze the linear size of the bodies of participated cow used in the progeny test of dairy cows in KAN Jabung, Malang, East Java. The material used consisted of 180 lactating cows emplyed as participated cows. The research employed was a survey with data collection throught purposive sampling, selecting cows that are lactating based on specific criteria. The data were analyzed using correlation analysis and simple linear regression. The results of the study, revealed correlation values between body weight, chest circumference, body length, height with body condition score (BCS), as follows: 0,3542; 0,3523; 0,1926; 0,3198 respectively. Meanwhile, the correlation values of chest circumference, body length, and height with body were found to be: 0,9990; 0,5381; 0,4528, respectively. In conclusion, this study determined that the highest correlation of participated cow linear body size was observed in the relationship between chest circumference and body weight, while the lowest correlation was found in the relationship between body length and BCS.